A Double Scale Methodology to Investigate Flow in Karst Fractured Media via Numerical Analysis: The Cassino Plain Case Study (Central Apennine, Italy) - M. Lancia; M. Saroli; M. Petitta (Geofluids)
A methodology to evaluate the hydraulic conductivity of the karst media at a regional scale has been proposed, combining pumping tests and the hydrostructural approach, evaluating the hydraulic conductivity of fractured rocks at the block scale. Obtaining hydraulic conductivity values, calibrated at a regional scale, a numerical flow model of the Cassino area has been developed, to validate the methodology and investigate the ambiguity, related to a nonunique hydrogeological conceptual model. The Cassino plain is an intermontane basin with outstanding groundwater resources. The plain is surrounded by karst hydrostructures that feed the Gari Springs and Peccia Springs. Since the 1970s, the study area was the object of detailed investigations with an exceptional density of water-wells and piezometers, representing one of the most important karst study-sites in central-southern Italy. Application of the proposed methodology investigates the hydraulic conductivity tensor at local and regional scales, reawakening geological and hydrogeological issues of a crucial area and tackling the limits of the continuum modelling in karst media.